Technology and law enforcement from gumshoe to gamma rays - Snow, Robert L.; Praeger Security International (Westport, Conn. Praeger Publishers, 2007)
"Using many real-life examples and first-hand anecdotes, this book takes readers through every major branch of law enforcement and shows how technology radically changed police department operations during the last two decades. It also shows how these changes continue today as technology advances and refines techniques already in practice. Beginning with the Night Stalker case, the author illustrates how the use and reliance on new technologies in solving crimes has made policing and detective work more accurate and efficient in capturing and convicting criminals and, more recently, how it has aided courts in releasing innocents convicted of crimes." --R?esum?e de l'?editeur.
Titre de l'?ecran-titre (visionn?e le 3 f?evrier 2011)
In Praeger Security International
Bibliogr.: p. [171]-181.
Publi?e aussi en version papier
Keywords: Enqu?etes criminelles -- Innovations -- Etats-Unis.; Lois -- Application -- Innovations -- Etats-Unis.; Police -- Etats-Unis -- Appareils et mat?eriel.